PENGARUH POLA ASUH OTORITER TERHADAP PRILAKU MEROKOK SISWA KELAS XII DI SMK N 02 KOTA TANGERANG SELATAN - Efi Retno Rahayu; Oryza Intan Suri (STIKes IMC Bintaro, 2019)
According to the world health organisation , who are the people of teenagers in the age range of 10-19 years .In the world it is estimated that the population of the teenagers were 1.2 billion atau18 % of the total of the world population , according to the health minister for ri no 25 years 2014 , according to global youth tobacco survey ( gats ) 2011 showed prevalence of smokers age of 15 up very high , among other male smokers ( 67.4 % ) and women ( 2.7 % ) , the role of parents in a house so critical to the development of children behavior and personality , a pattern of foster parents who applied at home is different every parents. The study aimed to identify the influence of the authoritarian civil against smoking student of class XII in SMK N 02 Kota Tangerang Selatan, The kind of research is using the quantitative approach with the analytic research survey design cross sectional. The sample collection of using formulas slovin sample 93. sampleResearch instruments used is the. Sheets Engineering an analyzer used for aware of the influence of using t. testSome of the data analysis obtained the number of civil smoked on teenagers with a pattern of some authoritarian 39 (48,1%), light smokers 38 (46,9%) smokers and percent 4 (4,9%). heavy smokersBased on the analysis t test obtained p-velue ( 0,002 < 0,05 ) so we can conclude there are significant influence of a pattern of authoritarian with civil. youth smoking.